2011
DOI: 10.2337/dc10-1392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Urinary Liver-Type Fatty Acid–Binding Protein in Diabetic Nephropathy of Type 2 Diabetic Patients

Abstract: OBJECTIVEUrinary liver-type fatty acid–binding protein (L-FABP) is a promising indicator of tubular but not glomerular damage. The aim of this study was to evaluate the clinical usefulness of urinary L-FABP as a prognostic biomarker in impaired diabetic nephropathy in type 2 diabetes.RESEARCH DESIGN AND METHODSThis investigation involved a cross-sectional and longitudinal analysis of the relationship between urinary L-FABP levels and progressive nephropathy. Urinary L-FABP was measured with enzyme-linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 9 publications
3
118
0
2
Order By: Relevance
“…Although several studies have reported associations of L-FABP with renal outcomes in adults with diabetes (16,17), associations of L-FABP with clinical outcomes have not been widely studied among patients without diabetes. Characteristics of L-FABP in our study sample suggest that there are differences in the analysis and interpretation compared with prior work in persons with diabetes, because a substantial proportion of our study population had L-FABP values that were below the lower LOD established in our performance laboratory, requiring us to model L-FABP categorically rather than continuously.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported associations of L-FABP with renal outcomes in adults with diabetes (16,17), associations of L-FABP with clinical outcomes have not been widely studied among patients without diabetes. Characteristics of L-FABP in our study sample suggest that there are differences in the analysis and interpretation compared with prior work in persons with diabetes, because a substantial proportion of our study population had L-FABP values that were below the lower LOD established in our performance laboratory, requiring us to model L-FABP categorically rather than continuously.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, biomarker studies to identify the presence and predict the progression of diabetic nephropathy have been investigated worldwide (15). Recently, Kamijo-Ikemori et al reported that urinary levels of liver-type fatty acid-binding protein (L-FABP) accurately reflected the 6 severity of diabetic nephropathy in type 2 diabetes (16). Importantly, urinary L-FABP levels were high in the patients with normoalbuminuria, suggesting its usefulness to detect earlier nephropathy in these patients.…”
Section: Biomarkers For Diabetic Nephropathy and Disease Progressionmentioning
confidence: 99%
“…Results demonstrated that the level of u-LFABP reflects the severity of DN (P< 0.05). High u-LFABP level was considered a risk factor for the progression of DN (adjusted HR 7.285, 95% CI 2.425 -21.883, P < 0.0001), suggesting its ability as an early screening tool as well as predictor of DN [61]. Although these findings introduce u-LFABP, a urinary marker of tubular inflammation, as a supplement to albuminuria in predicting DN development in both type 1 and type 2 diabetic patients, other studies produced contradicting results [62].…”
Section: Urinary Markersmentioning
confidence: 99%
“…These results should be intercepted with caution since u-LFABP was analyzed in a single 24h urine sample, urine samples were in a single 24h urine sample, urine samples were frozen at -20°C for ~18 years before analysis and urine samples before 1990 were lost so the analyzed urine samples were from 1990-2008 (although this is thought to only underrate the predictive power of u-LFABP) [60]. Moreover, another group of investigators assessed u-LFABP in predicting DN development in type 2 diabetic patients [61]. It included both a cross-sectional analysis, including 140 type 2 diabetic patients and 412 healthy individuals, and a longitudinal analysis, where 104 patients were followed for 4 years.…”
Section: Urinary Markersmentioning
confidence: 99%